Distribution and kinetics of the Kv1.3-blocking peptide HsTX1[R14A] in experimental rats - Ralf Bergmann (Nature Portfolio, 2017)
Abstract The peptide HsTX1[R14A] is a potent and selective blocker of the voltage-gated potassium channel Kv1.3, which is a highly promising target for the treatment of autoimmune diseases and other conditions. In order to assess the biodistribution of this peptide, it was conjugated with NOTA and radiolabelled with copper-64. [64Cu]Cu-NOTA-HsTX1[R14A] was synthesised in high radiochemical purity and yield. The radiotracer was evaluated in vitro and in vivo. The biodistribution and PET studies after intravenous and subcutaneous injections showed similar patterns and kinetics. The hydrophilic peptide was rapidly distributed, showed low accumulation in most of the organs and tissues, and demonstrated high molecular stability in vitro and in vivo. The most prominent accumulation occurred in the epiphyseal plates of trabecular bones. The high stability and bioavailability, low normal-tissue uptake of [64Cu]Cu-NOTA-HsTX1[R14A], and accumulation in regions of up-regulated Kv channels both in vitro and in vivo demonstrate that HsTX1[R14A] represents a valuable lead for conditions treatable by blockade of the voltage-gated potassium channel Kv1.3. The pharmacokinetics shows that both intravenous and subcutaneous applications are viable routes for the delivery of this potent peptide.